Peningkatan Kemampuan Mengenal Lambang Bilangan 1-20 Melalui Multimedia pada Peserta Didik Tunagrahita - Andono, Adnan Tri; Mahdi, Arisul (Universitas Negeri Padang, 2024)
This article discusses improving the ability to recognize the symbols for numbers 1-20 through multimedia for mentally retarded students. This research uses a quantitative research approach with experimental methods in the form of Single Subject Research (SSR) with an A1 (Baseline) - B (Intervention) - A2 (Baseline) design. The data was analyzed using graphic visual analysis techniques. Data collection techniques include tests and data collection tools for test questions. The subjects of this research were mentally retarded students in Class 2 SDLB at SLBN Sri Soedewi Jambi. The results of the research show that in the baseline condition (A1), three observations were made and obtained percentages of 40%, 40%, 40%. In the Intervention condition (B), seven observations were made and obtained percentages of 65%, 75%, 85%, 85%, 85% and in the baseline condition (A2), three observations were made, students obtained percentages of 85%, 85%. .85%. Based on the research results, it can be concluded that the ability to recognize the symbols for numbers 1-20 increases through multimedia for children with intellectual disabilities.